PEMBINAAN ANAK PADA MASA PUBERTAS MENURUT PENDIDIKAN ISLAM - Cut Nya Dhin (Jurnal Ilmiah Didaktika, 2013)
Puberty period is a transition time to look for the identity. This period is really sensitive that also determines the children’s personality in the future. One that develops during this transitional time is Juvenile deliquency which is one of many serious social problems for many parents nowadays. This problem arises due to the lack of attention and knowledge of parents, teachers, and surrounding society to guide those problematic children. An effective solution to overcome this problem is by implementing Islam ic education which is taken from some values of Al-Quran and Hadits. The aim of this research is to know the vision of Islam in education to guide teenagers during their puberty period. This is a library research that analyzes some references from books, magazines, newspaper and articles related to the topic of this research. The result showed that puberty period is really a decisive period to determine the children’s future education. In Islam ic education the children are trained to be qualified students and have a wider point of view. To reach this goal, Islam ic education has done some developments in the aspects of faith, moral, physic, and psychology.